Faktor-Faktor yang Mempengaruhi Kepuasan Pengguna Jaminan Kesehatan Nasional: Factors Influencing User Satisfaction with the National Health Insurance - Anggreiniboti, Tanti; Primal, Def (Al Dzahab, 2025)
Purpose: This study aims to identify the factors influencing user satisfaction with the National Health Insurance in Indonesia. Design/Methodology/Approach: This is a quantitative study with an analytical method using a cross-sectional approach. The population in this study consists of Indonesian citizens, utilizing data from the 2014 Indonesian Family Life Survey (IFLS). The total sample used in this study is 5,041 respondents. Data processing is conducted using the Stata application, employing the logit analysis method. Findings: There is a positive and significant influence of healthcare facility utilization and health insurance ownership on user satisfaction with health insurance. However, out-of-pocket payments beyond regular insurance contributions and waiting time do not affect user satisfaction with health insurance. Research Implications: Policies are needed to anticipate dissatisfaction among health insurance users by minimizing additional costs beyond the regular insurance contributions. Efforts should also be made to reduce waiting times for healthcare services.